Interparticle Spacing Effect among Quantum Dots with High-Pressure Regulation - Ji-Chao Cheng; Ling-Yun Pan; Xiao-Li Huang; Yan-Ping Huang; Ying-Hui Wang; Shu-Ping Xu; Fang-Fei Li; Zhi-Wei Men; Tian Cui (Nanomaterials, 2021)
In this paper, we explore whether interparticle spacing affects steady-state and transient-state optical properties by comparing close-packed CdSe/ZnS–quantum dots (QDs) and CdSe/ZnS–QDs dispersed in polymethyl methacrylate (PMMA). High–pressure is an effective physical means to adjust the interparticle spacing of QDs, which may artificially expand the application of QDs further. The results under high–pressure indicate that it is the reduced interparticle spacing rather than the enhanced quantum confinement effect with volume compression that has a stronger effect on exciton relaxation of CdSe/ZnS–QDs. This work is hoped to help us further understand the effect of interparticle spacing among QDs in various integrated environments.